2019
DOI: 10.1017/9781108765015
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Goals: Their Impacts on Forests and People

Abstract: Understanding the impacts of SDG 16 on forests and people requires attention to the power dynamics that shape how all 17 SDGs are interpreted and implemented across the Global North and South.• As SDGs were agreed upon by nation states, SDG 16 places a strong emphasis on state power and the rule of law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…The risk of species loss reflects multiple factors -including habitat loss, modification and fragmentation, over-exploitation, interactions with other species and climate change -and combinations of all these factors (Selwood et al 2015). When a species is lost from a forest, the ecological processes that depend upon that species are lost with it; this reduces community resilience and can provoke further species losses (Dirzo et al 2014, Redford 1992.…”
Section: Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of species loss reflects multiple factors -including habitat loss, modification and fragmentation, over-exploitation, interactions with other species and climate change -and combinations of all these factors (Selwood et al 2015). When a species is lost from a forest, the ecological processes that depend upon that species are lost with it; this reduces community resilience and can provoke further species losses (Dirzo et al 2014, Redford 1992.…”
Section: Biodiversitymentioning
confidence: 99%
“…This does not include the value of nontimber forest products, or the value of domestic public-sector expenditure. In addition to external ODA flows, Whiteman et al (2015) report some USD 7.3 billion in public-sector forest expenditure in tropical and subtropical countries in 2010. As another comparison, consider palm oil: in 2016, the value of Indonesian palm oil exports was USD 18.1 billion (GAPKI 2017).…”
Section: Targets For Financial and Policy Instrumentsmentioning
confidence: 99%
“…In India, lower-caste working women are subjected to routine violence and sexual abuse by the upper castes (Jayal 2003, Kumari 2017. In Sweden, considered to be one of the most progressive countries in terms of gender equality indices, Lundgren et al (2001) found that nearly every second woman, at some point since her 15th birthday, has experienced violence at the hands of a man, regardless of ethnicity or social class. In Aotearoa, New Zealand, more than one-third of women (35.4 per cent) reported physical and/or intimate partner violence in her lifetime (Simon-Kumar et al 2017).…”
Section: Women's Rights Over Their Own Bodies -Targets 52 and 56mentioning
confidence: 99%
“…Access to reproductive health services, including family planning, has helped reduce poverty, contributed to improved nutrition and educational outcomes, and saved mothers' lives, benefitting not only women but society more generally. Supporting girls' and women's education and the prevention of HIV infections by providing contraceptives has been shown to reduce the number of births, and that in turn mitigates deforestation effects as less land is taken over for agriculture (Starbird et al 2016).…”
Section: Women's Rights Over Their Own Bodies -Targets 52 and 56mentioning
confidence: 99%
See 1 more Smart Citation